Belief in the Reformation Era: Reflections on the State of Confessionalization. Issue 1 (28th March 2018) - Puff, Helmut
Abstract : That Christian religion pervaded many, if not most, aspects of life in sixteenth-century Europe, even the lives of those who were not Christian, is undisputed. "From birth to death stretched a long chain of ceremonies, traditions, customs, and observances, all of them Christian or Christianized, and they bound a man in spite of himself, held him captive even if he claimed to be free, " as Lucien Febvre remarked in 1942 in The Problem of Unbelief in the Sixteenth Century . Most everyone, including the French writer François Rabelais—the subject of Febvre's study—understood their own existence within the divine order. Accordingly, "a world without God" made little or no sense. Even if, pace Febvre, early modern people occasionally entertained the idea that there was no God, individuals rarely faced charges of atheism, as Francisca Loetz has shown. Our task in researching early modern religion is, then, to chart religious thought, practice, and experience as a complex and capacious phenomenon—its scope, shape, contours, and dynamics.